Serpinema cayennensis n. sp. (Nematoda: Camallanidae), a parasite of the freshwater turtle Rhinoclemmys punctularia Daudin (Reptilia: Testudines: Geoemydidae) from French Guiana: morphology and phylogenetic relationships with other turtle-parasitising camallanids - Harnoster, Florence; Svitin, Roman; Preez, Louis Du (Zootaxa, 2019)
The genus Serpinema was erected from the genus Camallanus to include species parasitising freshwater turtles. Following this, the taxonomic status of Serpinema was challenged by different authors considering it as a subgenus or junior synonym of Camallanus. Several specimens of these nematodes were retrieved from the spot-legged wood turtle Rhinoclemmys punctularia from Cayenne, French Guiana. These specimens clearly differed from previously reported Serpinema and Camallanus species parasitising turtles by the number of caudal papillae, shape of spicules and development of vulvar lips. Based on morphological characters the nematodes were assigned to the genus Serpinema and described as a new species S. cayennensis n. sp. The description followed by the molecular data analyses based on 28S, 18S rDNA and cytochrome oxidase subunit 1 (COI) gene sequences.